Pengaruh Budaya Literasi Dan Minat Baca Terhadap Prestasi Belajar Siswa Kelas VIII SMP Negeri 6 Pematang Siantar - Anju Siregar; Debbi Petra Meyana Sitorus; Anton Luvi Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to gain knowledge regarding the influence of literacy culture and interest in reading on the learning achievement of class VIII students at SMP Negeri 6 Pematang Siantar. This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 24. The population in this research is as many as 171 students, and the sample used was 120 people. The sample collection technique used was property random sampling. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2). The results of this research state that: 1) there is a positive influence of literacy culture on student learning achievement. This result can be seen in the t test where the t value of parental income (0.206) > t table value (1.658096). 2) there is a positive and significant influence of reading interest on learning achievement. This result can be seen in the t test where the t value of social style (5.018) > t table value (1.658096) which means that this variable is significant. 3) literacy culture and interest in reading together influence learning achievement. This result can be seen in the F test where the Fcount value (12.694) > Ftable value (3.05). The R Square coefficient of determination test was found to be 0.178, which means that 17.8% of the variables of literacy culture and interest in reading influence the learning achievement of class VIII students at SMP Negeri 6 Pematang Siantar and 82.2% is the influence of other variables not examined in this research.